Hubungan Tingkat Pengetahuan Ibu Nifas Primipara Dengan Sikap Ibu Tentang Perawatan Luka Jahitan Perineum Di PMB Bd. G. A Nyoman Candra, S.ST. Desa Dawuhan Lor Kecamatan Sukodono Kabupaten Lumajang - Ika Maratus Solihah; Anik Purwati; Reni Retnaningsih (KHD Production, 2024)
The postpartum period is the recovery period after the mother gives birth. The uterus will contract until it is the same size as the uterus before pregnancy. The postpartum period is the period that the mother will go through after childbirth, which starts after the birth of the baby and placenta, namely after the end of the fourth stage of labor and ends up to 6 weeks (42 days) which is marked by the cessation of bleeding. During the puerperium period, the reproductive organs must be cared for properly in order to prevent infection during the post partum period. The method used is a quantitative method with a research design in the form of a cross sectional approach. The aim was to find out whether there was a relationship between the level of knowledge of primiparous postpartum mothers and attitudes regarding perineal suture wound care at PMB Bd. G. A Nyoman Candra, S.ST. Dawuhan Lor Village, Sukodono District, Lumajang Regency. The results of statistical tests using the Spearman Rank test showed a p-value of 0.000, because the p-value < α (0.05) then H0 was rejected and Ha was accepted, which means there is a relationship between the level of knowledge of primiparous postpartum mothers and the mother's attitude regarding care for perineal suture wounds in PMB Bd. G. A Nyoman Candra, S.ST. Dawuhan Lor Village, Sukodono District, Lumajang Regency with a correlation coefficient of 0.693. The conclusion from the research results was that there was a relationship between the level of knowledge of primiparous postpartum mothers and the mother's attitude regarding the care of perineal suture wounds at PMB Bd. G. A Nyoman Candra, S.ST. Dawuhan Lor Village, Sukodono District, Lumajang Regency in 2024.